Batch and Flow Injection Spectrophotometric Methods for the Determination of Clonazepam in Pharmaceutical Preparations via Oxidative Coupling with Pyrocatechol - Q. Al-Abachi, Mouayed; Abdulwaha Hammoudi, Maysaa (Iraqi Journal of Science, 2023)
A simple, fast, and sensitive batch and flow injection spectrophotometricmethods have been developed for the determination of clonazepam(CZP) in pureform and in pharmaceutical preparations. The proposed methods are based on theoxidative coupling reaction of the reduced clonazepam using Zn powders and conc.HCl with payrocatechol and in the presence of ferric sulphate. The resulting reddishcolored product had a maximum absorbance at 515 nm. The optimum reactionconditions and other analytical parameters have been evaluated . The linear rangesfor the batch and FI methods determination of CZP were 0.5-32, 50-400 μg mL-1and the detection limits were 0.193, 22.60 μg mL-1 for both methods respectively.Statistical analysis of the results and comparison with results by the BritishPharmacopoeia method are also reported.